An Analysis of Six Standard Ontology Editing Tools for Capturing Entire Crop Processing - Ukpe, Emmanuel; S.M.F.D, Syed Mustapha (2016)
In the past decade, the ontology development community has witnessed several platforms and tools for ontology building. All these tools facilitate ontology development processes and direction for the subsequent usage. However, research has shown that current ontology editors do not effectively capture agricultural processes. Existing ontology editors do offer explicit but incomplete agricultural process information. This research proposes the need for a new ontology editor for process capturing, specifically capable of capturing entire cassava plantation process, which can be used to develop Intelligent Tutoring System (ITS) for farmers on crop processing. To this end, this paper examines, analyzes and presents the results of selected ontology editors. The comparison was done using different criteria including an ontology editor’s strength, weakness and suitability for capturing entire crop plantation process. Keywords: Ontology editors, Ontology, Protégé, Apollo, KAON2, SWOOP, WebOnto & Ontolingua